THE MEASUREMENT DESIGN OF READINESS LEVEL FOR TECHNOWARE AND HUMANWARE IN LABORATORY TO ACHIEVE THE REQUIREMENT FOR SNI ISO/IEC 17025 - ISLAM (NIM : 23410019) ; Pembimbing : Prof. Dr. Ir. Dradjad Irianto, M.Eng, SAEFUL
ASEAN Economic Community (AEC) is becoming an integrated economy, where flow of certain good, service, investment, and labor are free. In this context, certification or official approval of product plays an important role. This official approval must be given by an appropriate organization by assessing certain specific requirement so that the certified products are guaranteed to pass the minimum standard level. This requirement is also applied to testing and calibrating laboratories. To meet the recognition both nationally and internationally, testing and calibrating laboratories have to be accredited by National Accreditation Committee (KAN) that uses ISO / IEC 17025 as the reference for acreditation. For each laboratory, there are two important factors to be considerable for accreditation, i.e. technoware which relates to the advancement of machines and equipment, and humanware which related to the competence of human resources. To prepare Indonesian laboratories for accreditation, a study to measure the readiness level for technoware and humanware in laboratory is needed. This thesis is aimed at designing a measurement method of readiness level for technoware and humanware in laboratory to achieve the requirement for SNI ISO/IEC 17025. We used the degree of advancement of technoware and humanware as in UNESCAP (1989). The Quality Function Development (QFD) is used to relate the degree of technoware and humanware as in SNI ISO/IEC 17025 to the level of laboratory capability. The design was implemented to testing laboratory, environment laboratory, and calibration laboratory at the Center for Textile which are qualified as accredited laboratories certified by National Accreditation Committee (KAN). As the result, for technical responses laboratory, there are two processes (i.e. sample calibration and sample preparation) from eleven processes in technoware that do not meet the SNI ISO/IEC 17025 requirements. Meanwhile, there are only one process (i.e. assessment order) in humanware level that does not meet the SNI ISO/IEC 17025 requirement.